Planes Nacionales de Desarrollo en Costa Rica (2015-2022): un análisis de la perspectiva de innovación - Soto Kiewit, Luis Diego (2021)
In the current context, as a part of the development programs of the countries of Latin America, the figure of innovation appears, as a nodal element of the strategies to solve the difficulties of economic growth or to access the -haunted- development. With this frame, the objective of this article is to analyze the innovation perspective in the last two National Development Plans (PND) in Costa Rica. In methodological-technical terms, a discourse analysis is made of these documents, which follow the ideological-political line of two periods of government of the Partido Acción Ciudadana (PAC). The central conclusion of the article is that the notion of innovation present in the National Development Plans is general and unclear, which suggests a legitimate and ideological use of the lines of action established as priorities within the work agenda of both governments.